2021
DOI: 10.52728/ijtc.v2i1.208
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Accounting Information System Afflication In Reliability Financial Reporting

Abstract: The manifestation of regional financial autonomy can be seen in the regional financial accounting information system as a good government system characterized by increasingly low problems so that the information generated by the central government and regional governments in Indonesia is a form of quality financial reporting and effective application of accounting systems by various government agencies in Indonesia. Indonesia. This study aims to find out how the successful application of accounting information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…Majority of studies found that customer accounting information and companies' performance. For example, Safkaur, Yanti, Fery, and Azwardi, (2021) the outcomes of this look at display empirical proof that the a success software of financial reporting and AIS is accountable and transparent. DO, LUONG, and TRAN (2020) indicated that tourism companies have to pay much attention to the usage of information of management accounting in making decision.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Majority of studies found that customer accounting information and companies' performance. For example, Safkaur, Yanti, Fery, and Azwardi, (2021) the outcomes of this look at display empirical proof that the a success software of financial reporting and AIS is accountable and transparent. DO, LUONG, and TRAN (2020) indicated that tourism companies have to pay much attention to the usage of information of management accounting in making decision.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Moreover, AIS contributes to the reliability of financial reporting, enhances decision-making abilities based on relevant information, and increases flexibility in creating accounting reports (NguyenThanh et al, 2020). The successful application of AIS involves utilizing the system for various managerial tasks and ensuring user satisfaction with the generated information (Hertati et al, 2021). Organizations are increasingly designing sophisticated AIS to meet strategic goals and enhance overall performance (Naranjo, 2004).…”
Section: Definitions and Conceptsmentioning
confidence: 99%
“…This means that companies must view customers as a stream of revenue, a source of profit, over a series of long-term repeating transactions. Building relationships with customers can increase their lifetime profitability (Hertati, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%